Risk Management and Service Management Strategies for Car Rental in Improving Vehicle Security Quality for the Company - I Gede Panji Krisnayana (Green Publisher Indonesia, 2024)
The shift in tourist interest from initially using transportation services through travel agents to now preferring to rent vehicles themselves has become evident. With the increasing number of consumers requiring car rental services and companies expanding their fleet sizes, it is undeniable that the associated risks also increase each year. Therefore, the purpose of this research is to explore the complex risks to vehicle units in car rental companies in Bali and to determine strategies and steps to improve the security quality of vehicle units in these companies. This study employs a descriptive qualitative method with an enterprise risk management approach, which includes risk identification, risk analysis, risk assessment, risk management, and risk monitoring. The research results, using the likelihood impact matrix technique on five car rental companies in Bali, identified four common risks: operational risk, financial risk, human resources risk, and external risk, with varying levels of risk from low risk, medium risk, to high risk. Strategies for managing these risks include mitigating medium risks and accepting low risks. The policies derived from this study are in the form of risk analysis and risk management strategies for car rental companies in Bali to enhance the security quality of their vehicle units.